RACISMO E NECROPOLÍTICA: a lógica do genocídio de negros e negras no Brasil contemporâneo - Francilene Cardoso (Universidade Federal do Maranhão, 2018)
This paper aims to analyze black´s genocide logic due to capital actual transformations. This study is based on Karl Marx (2011; 2013), Robert Kurz (1992),Mészaros (2005) analysis of merchandise´s fetishism, in order to understand bourgeois society contradictions and socioeconomic basement where racism is set. Barbarism is the key to analyse contemporary capitalism(MENEGAT, 2006), whose crisis produced from one side a big excessed population mass and from the other side social control attempts and the raise of genocide, trough necropolitics , a solution to control and eliminate physically this mass who have not function for capital reproduction(MBEMBE, 2011).